INTERPRETASI POLA ANOMALI GAYA BERAT REGIONAL KAITANNYA TERHADAP POTENSI SUMBER DAYA GEOLOGI DI LENGAN SELATAN SULAWESI - Subagio Subagio; Bambang S. widijono (Jurnal Geologi dan Sumberdaya Mineral, 2012)
The research area is part of Western Sulawesi Geological Terrain, arranged by pre-Tertiary to Quarternary rocks. The pre Tertiary rocks exposed in Latimojong Mountain located at northeastern research area and Maros Mountain near Bantimala district at southwestern area. The pre Tertiary rocks consist of metamorphic, and ultrabasic rocks overlain by flysch sediments. These flysch sediments overlain by Paleogen terrestrial sediments and carbonate rocks. The Oligosen - Early Miosen rocks exposed at Bone Mountains. These rocks consist of clastic and volcanic clastic sediments. The carbonate rocks have also been faund in that area. The Middle Miosen - Pliosen clastic sediments exposed along the valley in Graben Wallanae. The Quarternary sediments is distributed in Wallanae River. Regional gravity anomalies indicate the main lineaments geological structure that developed in the study area. The lineaments are north-south, northwest-southeast, and north northwest-south southeast directions. Wallanae fault is indicated by north-south direction indicating parallel contours anomaly that separate high anomaly in the west and low anomaly in the east of Wallanae Fault. The high anomaly pattern indicates the occurrance of ultramafic basement rock with having a mass density 2.9 gr/cc, while low anomaly indicates the occurrence of metamorphic basement rock with having mass density 2,8 gr/cc. The undulation of residual anomaly reflects the straightness of shallow geological structures. The geological resources of the region area are hydrocarbon, coal, and metallic minerals. This hydrocarbon probably present in the low anomaly, coal in the marginal basinal anomaly, while metallic mineral is found at high anomaly area.Key words : Lineament, anomalies, basement rocks, geological resources, Sulawesi